EVALUATION OF RECOMBINANT EXPRESSION OF CODA GENE REGULATED BY RD29A PROMOTER IN TOBACCO - Thi Thu Huong, Bui; Huy Gioi, Dong; Manh Dung, Ngo; Bich Ngoc, Pham; Hoang Ha, Chu (Journal of Forestry Science and Technology, 2019)
There are many evidences showing the fact that some hard conditions from environment, namely abiotic stress, could make several significantly negative impacts on crop production. However, some plant species can overcome these bad situations by complicated mechanisms. The reason is that there are genetically valuable factors in their cells enhancing their stress tolerance. This study has shown the result of the construction the recombinant vector carrying CodA gene which could encode an enzyme, named choline oxidase, and is controlled by Rd29A promoter. The vector with Rd29A/CodA cassette was transformed into Agrobacterium tumefaciens C58 strain and used to mediate with K326 Nicotiana tabacum. The tobacco lines transformed sucessfully the structure could stimulate a biosynthesis of high amount glycinebetaine, the chemical can improve stress tolerance of plants. Specifically, eight transgenic lines (3, 4, 5, 6, 8, 9, 15, and 16) were confirmed the presence of CodA gene by PCR using a CodA specific primer pair and tested with in vitro stress assays. The collected data had confirmed that some Rd29A/CodA transgenic tobacco lines illustrating the resistance of them to some stresses and accumulated 6 to 7 times higher amount of glycinbetaine in artificially salty and drought mediums supplemented with NaCl 250mM or 2.5% PEG6000, respectively, than those in normal state.